Public Health Spending and Health Outcomes in Kenya - James Murunga; Evans Geoffrey Mogeni; Dorothy Ngina Kimolo (European Scientific Journal, ESJ, 2019)
Health is important for sustainable economic performance of a country. This study seeks to investigate the effectiveness of public health spending on health outcomes. This is obtained by estimating a health production function for Kenya. In the study, infant mortality rate is used to measure health outcomes. The study uses time series data running from 1984 to 2015. The data is obtained from World Bank database and Kenya National Bureau of Statistics Economic Surveys. Error Correction Model (ECM) is adopted due to presence of cointegration. The results show that public expenditure on average influence health outcomes in Kenya. These results therefore provide evidence to support that increase in public expenditure improves health outcomes. The other factor that is found to be important determinant of health outcomes in Kenya is child immunization. The major policy implication of this study is that Kenyan government should increase budgetary allocation to health sector. In addition, government of Kenya should allocate more resources to child immunization.